Generation Ungewiss: Berufseinsteiger auf dem Weg ins Abseits? Empirische Vergleiche zur Chancenentwicklung von befristet beschäftigten Arbeitsmarkteinsteiger/innen - Marie-Christine Fregin (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
– This paper examines the effect of changing labor market conditions and individual characteristics on early labor market career results. More precisely, it tackles the chances for a transition from fixed-term to permanent employment during the professional start-up phase and explores explaining factors. Longitudinal data of the SOEP (survey years 1990-2010) are used to conduct an empirical investigation. Several theory-based hypotheses are being tested by means of descriptive analysis and multivariate nested discrete-time survival analysis models. Findings suggest that the timing of labor market entrance has hardly any effect on the transition from fixed-term to permanent work. The stock of human capital (level of formal qualification) has a statistical highly significant impact on transitions: compared to those with a middle qualification level, people with a high and a low educational qualification do have poorer chances of contracts for an indefinite term. Public employees have poorer chances than other employees. There is no statistical evidence for the effects of the variables sex, migration background, age and size of corporation. In contrast, higher regional unemployment rates decrease, a growth of GDP increases the opportunity for a transition to permanent employment.
Keywords: 330; Befristung; atypische Beschäftigung; Kohortenvergleich; Arbeitsmarkteinstieg; labor market; atypical employment; fixed-term contracts; professional start-up; labor market entry